2020
DOI: 10.5194/se-11-1399-2020
|View full text |Cite
|
Sign up to set email alerts
|

Frictional slip weakening and shear-enhanced crystallinity in simulated coal fault gouges at slow slip rates

Abstract: Abstract. Previous studies show that organic-rich fault patches may play an important role in promoting unstable fault slip. However, the frictional properties of rock materials with nearly 100 % organic content, e.g., coal, and the controlling microscale mechanisms remain unclear. Here, we report seven velocity stepping (VS) experiments and one slide–hold–slide (SHS) friction experiment performed on simulated fault gouges prepared from bituminous coal collected from the upper Silesian Basin of Poland. These e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 98 publications
(144 reference statements)
0
3
0
Order By: Relevance
“…5, highlights that there are instances in the literature of strainrelated induced maturation in both amorphous and graphitic carbon. Of particular interest is the work of Fan et al (2020) that show the shift of the RBS parameter because of the increase of effective normal stress in friction isothermal experiments (Fig. 5 c,d) as already outlined by Maslova et al (2012).…”
Section: Raman Shift In Faulted Rocks: Difference Between Seismic And...mentioning
confidence: 79%
See 2 more Smart Citations
“…5, highlights that there are instances in the literature of strainrelated induced maturation in both amorphous and graphitic carbon. Of particular interest is the work of Fan et al (2020) that show the shift of the RBS parameter because of the increase of effective normal stress in friction isothermal experiments (Fig. 5 c,d) as already outlined by Maslova et al (2012).…”
Section: Raman Shift In Faulted Rocks: Difference Between Seismic And...mentioning
confidence: 79%
“…Looking at the Raman shift in experiments, it can be observed that frictional heating by rotary shear, generally yield higher R1 values after shearing (Fig. 5 c; Furuichi et al, 2015;Hirono et al, 2015;Ito et a., 2017;Fan et al, 2020), except in the work of Kuo et al (2017). Also, an increase in the RBS values (Fig.…”
Section: Raman Shift In Faulted Rocks: Difference Between Seismic And...mentioning
confidence: 92%
See 1 more Smart Citation